The Soybean GmNARK Affects ABA and Salt Responses in Transgenic Arabidopsis thaliana - Cheng, Chunhong; Li, Changman; Wang, Diandong; Zhai, Lifeng; Cai, Zhaoming (Frontiers in Plant Science, 2018)
GmNARK (Glycine max nodule autoregulation receptor kinase) is the homolog of Arabidopsis thaliana CLAVATA1 (CLV1) and one of the most important regulators in the process of AON (Autoregulation of Nodulation), a process that restricts excessive nodule numbers in soybean. However, except for the function in AON, little is known about this gene.Here, we report that GmNARK plays important roles in process of plant response to abiotic stresses. Bioinformatic analysis and subcellular localization experiment results showed that GmNARK was a putative receptor like kinase and located at membrane. The promoter of GmNARK contains manifold cis regulatory elements that are responsive to hormone and stresses. Gene transcript expression pattern analysis in soybean revealed GmNARK was induced by ABA and NaCl treatment in both shoot and root. Overexpression of GmNARK in Arabidopsis resulted in higher sensitivity to ABA and salt treatment during seed germination and greening stages. We also checked the expression levels of some ABA response genes in the transgenic lines; the results showed that the transcript level of all the ABA response genes were much higher than that of wild type under ABA treatment. Our results revealed a novel role of GmNARK in response to abiotic stresses during plant growth and development